Fried Chicken Consumer’s Preference and Purchase Decision Analysis During Covid 19 Pandemic Era - Febrianisa Yulia Sandita; Ibnu Wahid Fakhrudin Aziz; Mirwan Ushada (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2022)
This study aims to observe the decision-making process on fried chicken purchases, and identify the most considered attribute, and combination of attributes based on consumer preference in the Covid-19 pandemic era. The pandemic has altered consumer behavior and consumption patterns, leading to changes in the food industry. Understanding how consumer preferences have shifted can help businesses adapt their strategies to better serve their customers. The data were collected using the questionnaire method through the Google Form platform with respondent criteria being fried chicken consumers who had purchased fried chicken at least twice in the last six months with the number of respondents being 135. The questionnaire consisted of two parts, the first part is about the consumer's purchase decision-making process and the second one is about the consumer's preference for fried chicken. Price, serving, purchase state, and packaging are the attributes chosen to identify consumer preferences using the conjoint analysis method. This study shows consumer habits in the decision-making process of buying fried chicken and consumers’ preferences toward the price, serving, purchase state, and packaging of fried chicken. Product attributes were the most considered based on importance level Price (40.73%), Purchase state (33.57%), Serving (16.99%), and Packaging (8.70%). The combination of fried chicken product attributes that are preferred by consumers according to the utility value of each level attribute is less than 15.000 IDR of price, served with rice/fried chicken and vegetables, purchased in ready-to-eat (takeaway/delivery) form and using paper box packaging.